Aetiology and Short-term Outcome of Altered Level of Consciousness among Patients in Medicine Department of a Tertiary Hospital - Sarker, Partha Sarathi; Rahman, Md Saidur; Biswas, Palash Kumar; Chowdhury, Md Monjurul Kader; Chowdhury, Md Muntasir Islam; Karmaker, Madhabi; Azad, Khan Abul Kalam (Journal of Medicine, 2017)
Background: Altered level of consciousness is a very common medical emergency resulting in considerable mortality & morbidity. Accurate diagnosis & prompt management can reduce the complications to a great extent. There are various aetiologies of impaired consciousness including infective & metabolic causes as well as cerebrovascular accidents. This study described clinical outcomes of the patients relating to specific aetiologies of the illness. Objectives: To explore the common aetiologies of altered consciousness & to determine the clinical outcomes of the patients after one month in a tertiary level hospital of Bangladesh. Methods: This hospital based prospective observational study was conducted in Medicine department of Dhaka Medical College Hospital (DMCH) from December 2013 to May 2014. Sample size was 100 & the data was collected by structured questionnaire. Purposive sampling method was applied using inclusion & exclusion criteria. Statistical analysis of the result was obtained by using SPSS-16. Results: The mean age of the study patients was found 48.7 years with range from 19-92 years. Majority (58%) of the patients were male. Stroke was identified as the commonest (39%) aetiology of impaired consciousness followed by meningo-encephalitis (19%), septicemia (10%) & poisoning (10%). Among metabolic encephalopathy diabetic ketoacidosis was 3%, hypoglycemia 1% and hepatic, uremic & hypertensive encephalopathy was 3%, 4% & 1% respectively. Overall death rate was higher among patients with stroke (26%), ICSOL (50%), ADEM (50%) than those with meningoencephalitis (5.3%), septicemia (20%) & poisoning (10%). Conclusion: Infective & metabolic causes of impaired consciousness showed better outcome than structural & vascular aetiologies of brain. J MEDICINE July 2017; 18 (2) : 80-85